The Function of Astrocyte Mediated Extracellular Vesicles in Central Nervous System Diseases - Gharbi, Tahereh; Zhang, Zhijun; Yang, Guo-Yuan (Frontiers in Cell and Developmental Biology, 2020)
Astrocyte activation plays an important role during disease-induced inflammatory response in the brain. Exosomes in the brain could be released from bone marrow (BM)-derived stem cells, neuro stem cells (NSC), mesenchymal stem cells (MSC), etc. We summarized that exosomes release and transport signaling to the target cells, and then produce function. Furthermore, we discussed the pathological interactions between astrocytes and other brain cells, which are related to brain diseases such as stroke, Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS) disease, multiple sclerosis (MS), psychiatric, traumatic brain injury (TBI), etc. We provide up-to-date, comprehensive and valuable information on the involvement of exosomes in brain diseases, which is beneficial for basic researchers and clinical physicians.